A New Collector Chemistry For Phosphate Flotation - J. D. Miller; M. Li (Society for Mining, Metallurgy & Exploration, 2001)
Many technology problems must be solved if we are to continue to produce phosphate at our current rate of consumption. The U.S. produces at least 25% of the world's phosphate, 40 million tons of phosphate rock per annum with most of the production coming from Florida. Of particular concern are improved separation efficiency and the ability to treat new dolomitic resources. Phosphate flotation technology needs include: 1. Simplification of the standard flowsheet 2. Improved recovery of coarse phosphate 3. Selective flotation for phosphate recovery from dolomitic resources Preliminary results, including tests on plant feed from Florida show that these objectives may be achieved with a new collector chemistry depending on the specific circumstances. The effectiveness of the new collector chemistry has been demonstrated by the preliminary results from single stage flotation experiments both at the University of Utah laboratories and at Florida Institute of Phosphate Research (FIPR) laboratories. In the best case, from these experiments with low grade (5% P2O5) coarse feed (16x35 mesh), a single stage phosphate recovery of 95 % was achieved with a concentrate grade of 31 % P2O5. Such a separation efficiency could not be achieved using the traditional fatty acid/fuel oil collector. Based on these results it seems that a one step process may be possible for phosphate flotation and a research program is justified for the development of this new flotation strategy.